The Correlation between Stress and Mental-Emotional Disorders in Older Adults at the Geriatric Polyclinic of Udayana Level II Hospital, Denpasar - Puspa Dewi, Triyana; Yudhawati, Ni Luh Putu Suardini; Wardani, Silvia Intan; Serinadi, Desak Made; Madulara Martin, Neil (Universitas Nahdlatul Ulama Surabaya, 2025)
Mental-emotional disorder in older adults may arise as a result of stress that is not adequately managed. This study analyzes the correlation between stress and mental-emotional disorders in older people at the Geriatric Polyclinic of Udayana Level II Hospital, Denpasar. It used a quantitative method with a cross-sectional approach. The population consisted of 337 older adult patients receiving treatment at the Geriatric Polyclinic of Udayana Level II Hospital, with a sample size of 183 individuals. The sampling technique was purposive sampling. The Perceived Stress Scale (PSS-10) was an instrument to measure stress, and the Self Rating Questionnaire (SRQ-20) for mental-emotional disorders. The univariate analysis described the characteristics of the respondents, and the bivariate analysis evaluated the correlation between both variables using Spearman's rank correlation. Almost half of the respondents were 65-74 years old, 78 respondents (42.6%). Half of them were female, 99 respondents (54%). In addition, 62 or 33.88% of respondents graduated from a Senior High School. Most respondents experienced a moderate stress level of 134 respondents (88.5%) and mental-emotional disorders of 158 respondents (86.3%). Most respondents with moderate stress levels experienced mental-emotional disorder (66.12%). The Spearman's Rank Correlation obtained p=0.036 (p<0.05), indicating a significant correlation between stress levels and mental-emotional disorder in older people. Stress levels correlate with mental and emotional disorders in older people at the Geriatric Polyclinic of Udayana Level II Hospital, Denpasar. Efforts to recognize stress early, especially in older adults, are essential.